Students’ writing ability in descriptive texts and their problems of using appropriate adjective in SMP - Elfa Kirana; Hermawati Syarif; Desvalini Anwar (Fakultas Ilmu Pendidikan UNP)
This study aims to analyze the students' ability in writing descriptive texts in class VIII and the adjectives’ problems that they encountered in writing the texts. This study was a descriptive study and used cluster random sampling. The subject was thirty students in VIII. The test was used in collecting the data and was processed by using an assessment rubric of Heiton which evaluated five components of students’ writing ability. The findings show that nine students had good ability, three students had fair ability, fifteen students had poor ability and three students had very poor ability. Half of students had problems in using adjectives. The results showed that students still had difficulty in developing the content, organization, grammar, vocabulary, mechanics, and had the problems in adjective. Therefore, teachers are suggested to give exercises for students to write descriptive text.